The oldest guard: forging the Zionist settler past - Halperin, Liora R. (Stanford studies in Jewish history and culture, 2021)
Introduction : mother of the colonies -- Private farmers and the origins of "First Aliyah" claims-making -- Arab labor and the rhetoric of hierarchical coexistence in Mandate Palestine -- The old guard on display -- The colony and the village : constructions of coexistence after the Nakba -- Jewish immigrants and the politics of settler "First Ones," 1948-1967 -- Conclusion : thinking about the First Aliyah after 1967.